Periprosthetic joint infection of the knee complicated by primary localized cutaneous amyloidosis: a case report - Lai, Xinxuan; Zhang, Qianjin; Liu, Fuxin; Xu, Zhiqing; Guo, Jinhua; Qiu, Hanglin; Xu, Fudong; Zhuang, Zhikun; Huang, Changyu (Frontiers in Medicine, 2025)
BackgroundPrimary localized cutaneous amyloidosis (PLCA) is characterized by amyloid protein deposition in the skin, leading to pigmentation, papules, and itching. The etiology of PLCA remains unclear. Periprosthetic joint infection (PJI) post-total knee arthroplasty (TKA) poses challenges in management.Case presentationA PLCA patient underwent TKA and developed acute PJI, necessitating multiple surgical interventions. Recurrence of infection symptoms prompted a two-stage revision surgery approach.ConclusionSkin lesions in PLCA patients may potentially contribute to the risk PJI following arthroplasty. Strategies such as using tacrolimus for itching management, along with prophylactic antibiotics during PLCA flare-ups, could potentially aid in preventing and managing PJI in this patient population. Further research is needed to elucidate the relationship between PLCA and PJI post-arthroplasty.